Weak itinerant ferromagnetism and non-Fermi liquid behavior in Ni-TM (TM = Cr, Nb) alloys near critical concentration. (28th April 2021) - Vishvakarma, Sonu; Srinivas, V
Abstract: We report a comprehensive study on the magnetic, electrical and thermal properties of Ni100− x TM x ( TM = V, Cr, Nb, ) alloys around their critical concentration. Analysis of field and temperature dependence magnetization data suggests a weak itinerant ferromagnetic behavior in x = 8 and 10 compositions and the ferromagnetic ordering suppresses in the concentration range 10 < x < 12. Further, the temperature dependence of specific heat shows an unusual low temperature variation with an enhanced Sommerfeld coefficient, γ, with a signature of non-Fermi-liquid (NFL) behavior close to critical concentration. Further, the enhancement in Kadowaki–Woods ratio suggests it to be a strongly correlated electron system near critical concentration. Present analysis of experimental data consistently revealed that the NFL behavior is caused by spin fluctuations near critical concentration. The temperature dependencies of the electrical resistivity, the magnetization and linear term of the electronic specific heat appear to follow the theoretical predictions of a quantum phase transition and it is tempting to suggest that the presently studies Ni-rich alloys can be candidates for the observation of Griffith phase.